'Entering the world of academia is like starting a new life': a trio of reflections from Health Professionals joining academia as second career academics. Issue 1 (2nd January 2021) - Herman, Nicoline; Jose, Maria; Katiya, Misiwe; Kemp, Merlisa; le Roux, Natalie; Swart-Jansen van Vuuren, Claudia; van der Merwe, Charmaine
ABSTRACT: This research explored the experiences of three health professionals transitioning into academia as second-career academics (SCAs), with the aim of gaining insight into potential enablements and constraints for such career changers. The process of redefining identity from expert health professional to novice academic could occur through a three-stage process of transitioning. However, if SCAs experience an unsupportive or 'care-less' environment, such redefining may not occur. The paper attempts to illuminate the crucial role of educational developers in understanding and supporting SCAs when they 'start a new life' in academia.